Quality decreases from introducing patient choice in a National Health Service - Barros, Pedro Pita (2022)
A view often expressed about patient choice of health care providers is that it will increase competition between providers, which benefits the efficiency of the health system. We address here a patient choice initiative, regarding selection of hospital for specialty consultations, in the Portuguese National Health Service (NHS) that has two specific features. The first feature involves shared decision making between patients and GPs, in the choice of hospital for referral, which should be based on publicly available information on “quality”. The second specific feature is that the patient choice initiative did not involve payment changes to NHS hospitals associated with patients’ movements. We show that explaining initial asymmetries in qualities (waiting times) with systematic differences in hospital characteristics (cost advantages and managerial talent) leads to potential asymmetric responses to the introduction of patient choice in the NHS. This implies that the empirical analysis has to accommodate such asymmetries. Explicitly allowing for asymmetries in responses to the policy measure reveals that reactions were indeed different, with top-performance hospitals reducing their qualities (increasing waiting times) after the patient choice initiative was introduced.